TEACHING READING SKILL WITH BUSUU APPLICATION BASED: A CASE STUDY RESEARCH DESIGN SENIOR HIGH SCHOOL - Silviani Silviani; Moh Hafidz (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Reading instruction in junior high schools is often dominated by textbook-based and teacher-centered practices, limiting students' engagement and reading comprehension. Although previous studies have reported that the Busuu application improves vocabulary acquisition, learner autonomy, and learning motivation, little research has qualitatively examined how Busuu is implemented in reading instruction and how students respond throughout the learning process. This study aims to describe the implementation of the Busuu application in teaching reading skills and to explore students' responses to its use. A qualitative approach with a case study design was employed. The participants were 30 seventh-grade students at SMPN 1 Klampis, selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings revealed that Busuu was implemented through text introduction, vocabulary activities, reading practice, comprehension exercises, and immediate feedback. Students responded positively, reporting that the application was easy to use, enriched vocabulary, improved reading comprehension, and enhanced learning motivation and classroom participation. Despite limitations related to internet connectivity and device availability, the learning process remained effective. The novelty of this study lies in providing a comprehensive qualitative description of Busuu implementation and students' responses in junior high school reading instruction, offering practical insights for integrating digital learning applications into English classrooms. ABSTRAK Pembelajaran membaca bahasa Inggris di tingkat SMP masih didominasi oleh penggunaan buku teks dan pembelajaran yang berpusat pada guru sehingga keterlibatan siswa dalam memahami teks masih terbatas. Berbagai penelitian menunjukkan bahwa aplikasi Busuu mampu meningkatkan kosakata dan motivasi belajar, namun masih sedikit penelitian yang mengkaji secara mendalam proses implementasinya dalam pembelajaran membaca di kelas menggunakan pendekatan kualitatif. Penelitian ini bertujuan mendeskripsikan implementasi aplikasi Busuu dalam pembelajaran keterampilan membaca serta mengidentifikasi respons siswa terhadap penggunaannya. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Partisipan penelitian terdiri atas 30 siswa kelas VII SMPN 1 Klampis yang dipilih secara purposive. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Busuu diimplementasikan melalui kegiatan pengenalan teks, pembelajaran kosakata, latihan membaca, latihan pemahaman bacaan, serta pemberian umpan balik secara langsung. Siswa memberikan respons positif karena aplikasi mudah digunakan, memperkaya kosakata, meningkatkan pemahaman bacaan, serta mendorong motivasi dan partisipasi belajar. Meskipun terdapat kendala keterbatasan perangkat dan koneksi internet, pembelajaran tetap berlangsung efektif. Kebaruan penelitian ini terletak pada penyajian deskripsi komprehensif mengenai proses implementasi Busuu dan respons siswa dalam pembelajaran membaca pada konteks SMP sebagai acuan integrasi media pembelajaran digital.